Rancang Bangun Sistem Penghematan Biaya Listrik Pada Rumah Dengan Metode Finite State Machine Menggunakan Labview Berbasis Arduino - Puguh Bahtiar; Wijaya Kurniawan; Sabriansyah Rizqika Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Electrical energy is something very important to sustain human life. The availability of electrical energy and the growth of power plants is a two think that must be considered by every human. Based on these problems, there is an effort to prevent the occurrence of electrical energy crisis in the future, one of the efforts is to design the electricity saving on the house. Researchers use the finite state machine method with Arduino Uno as a hardware control and labview as a program design and implementation software. In this research, there is 6 features that are (1) Detect human existence by using PIR sensor. (2) automatically set room light. (3) Automatic water pump. (4) automatically set room temperature (5) Calculate and limit the use of electricity per day by limiting electricity consumption. (6) Sending notices for email and turn off the AC when electricity usage has reached the expenditure limit per day. The testing process on 6 features has been done, and the results obtained in accordance with the work function of each feature.